Simulating eroded soil organic carbon with the SWAT-C model. (April 2018) - Zhang, Xuesong
Abstract: The soil erosion and associated lateral movement of eroded carbon (C) have been identified as a possible mechanism explaining the elusive terrestrial C sink of ca. 1.7–2.6 PgC yr −1 . Here we evaluated the SWAT-C model for simulating long-term soil erosion and associated eroded C yields. Our method couples the CENTURY carbon cycling processes with a Modified Universal Soil Loss Equation (MUSLE) to estimate C losses associated with soil erosion. The results show that SWAT-C is able to simulate well long-term average eroded C yields, as well as correctly estimate the relative magnitude of eroded C yields by crop rotations. We also evaluated three methods of calculating C enrichment ratio in mobilized sediments, and found that errors associated with enrichment ratio estimation represent a significant uncertainty in SWAT-C simulations. Furthermore, we discussed limitations and future development directions for SWAT-C to advance C cycling modeling and assessment. Highlights: SWAT-C is able to simulate well long-term average eroded C yields. SWAT-C correctly estimated relative magnitude of eroded C yields by crop rotations. Errors associated with enrichment ratio estimation represent a significant uncertainty in SWAT-C simulations. Future SWAT-C development directions are discussed to advance watershed scale carbon cycling modeling and assessment.